Efektivitas Model Pembelajaran Berbasis Teams Games Tournament (TGT) dalam Meningkatkan Hasil Belajar IPS Siswa Kelas 7H MTsN 1 Kota Kediri - Nur Chamidah; Mutiara Arlisyah Putri Utami (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
Student learning outcomes in Social Studies (IPS) at Class 7H MTsN 1 Kota Kediri were initially low, due to the use of less interactive lecture methods. This led to low student motivation and difficulty in understanding the material. This study aims to improve students' learning outcomes in Social Studies through the application of the cooperative learning model Teams Games Tournament (TGT). The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model conducted in two cycles. The subjects were 33 students of Class 7H. Data collection techniques included tests, observation, and questionnaires. The results showed an improvement in student learning outcomes across each cycle. The average score increased from 64.84 in the pre-cycle to 79.24 in cycle I, and reached 94.27 in cycle II. The percentage of mastery learning also improved from 3.03% to 81.82%, and finally reached 100%. Therefore, the TGT learning model proved to be effective in improving students’ learning outcomes in Social Studies.